Property rights and the production of the urban built environment in Zambia - Munshifwa, Ephraim Kabunda (Department of Construction Economics and Management, 2015)
This study investigated the phenomenon whereby settlements with ostensibly similar socio- economic status exhibited significantly different physical outcomes, such as in the quality of houses, spatial arrangements and available services. The study investigated three related questions. Firstly, given the similarity in the levels of incomes, what is the relationship between property rights and physical development outcomes in low income settlements? Secondly, what are the underlying mechanisms and processes by which these physical developments are produced? Thirdly, what is the relationship between formal and informal institutions and organisations in the production of the built environment? Corresponding to these questions were three hypotheses. The first hypothesis was that, at any given level of average incomes, different strengths of property rights have differential effects on physical development outcomes. The second hypothesis was that different property rights are associated with different mechanisms and processes in the physical development process and thirdly that situations of extra-legal property rights require State mechanisms in the production of the built environment. Using a theoretical, conceptual and analytical framework provided by the new institutional economics, the study employed the comparative institutional analysis methodology to determine the influence of three types of property rights on the production of the built environment in Zambia. These rights were categorised as informal, semi-legal and legalised, and are to be found respectively in Mindolo North, Chipata and Ipusukilo, three settlements in Kitwe selected as case studies. Empirical data was collected using household surveys, focus group discussions, semi-structured interviews and observations. The study finds that stronger property rights are associated with better quality physical development outcomes. Furthermore, the study finds that different types of property rights are associated with different mechanisms and processes for the production of the built environment. Finally, the study finds that where property rights are extra- illegal or informal, successful development requires that there be facilitative interaction between formal institutions of the State at one hand, and informal institutions and organisations at the other.